Capabilities Without Rights? The Trespassing Project in Naples - Lavinia Bifulco; Raffaele Monteleone; Carlotta Mozzana (Social Work & Society, 2012)
The aim of this paper is to analyze a project for young NEET in southern Italy in terms of capabilities. Our objective is to examine to what extent it is possible to promote capabilities for work, for voice and for education in a context of lack of resources and rights as the one the project is rooted in. The paper focuses on the institutional, social and individual factors that hamper or promote the conversion of formal resources and rights into capabilities, and tries to understand what the outcomes are for beneficiaries. It highlights on the one hand the critical elements, and on the other the creation of innovative itineraries designed to promote such capabilities, trying to sum up lessons and indications in terms of policies, as well as theoretical and analytical implications for the capability approach.